Perfil de risco imunológico de idosas com câncer de mama - Vollbrecht, Betina (2015)
The elderly population is now the fastest growing in the world. The immune system becomes compromised with age, being less effective in fighting malignancies. An amended fee of CD8 T cells, increased compared to CD4 cells (usually more frequent in the blood) defines the concept of immune risk profile in the elderly (less than 1 ratio). In this research, we studied the immunological profile of 58 women with breast cancer, determining the ratio of CD4+/CD8+ in peripheral blood. We compare this link into groups according to age of the patient (less or more than 60 years), lymph node involvement, tumor size, the immunohistochemical profile, and the occurrence of adverse events (local recurrence, axillary recurrence and metastasis). The ratio of CD4+ /CD8+ lymphocytes average was 1.87 (1.1 to 3.32), therefore, no patient had a concept immune risk profile. Comparing the groups according to age, the presence of lymph node metastases, tumors smaller or higher than 2 cm, were no statistically significant differences. However, the CD4 / CD8 ratio in patients positive for human epidermal growth factor (HER-2 / neu) was higher than in samples of patients with hormone receptor positive carcinoma and Her-2 / neu negative (p = 0.036 ). As far as was possible to search, these are the first data on CD4+ and CD8 T+ cells specifically in a population with breast cancer. The increase in the number of CD4+/CD8+ current evidenced in these women with Her-2 carcinoma / neu positive, seems to signal an activation of the immune system in women with poor prognosis of tumors.